The Contemporary Role of the Global Refugee Regime: Analysis of Equal Protection Under South Africa’s National Refugee Regime - Callixte Kavuro (Obiter, 2024)
This article analyses the role of the global refugee regime in protecting both de jure and de facto refugees in South Africa, with a specific focus on the principle of equality at the national level. It refers to South Africa’s commitment to achieving equality, and to the interpretation of equality in the post-1994 constitutional order. Building on this, the article discusses the impact of the guiding standards of favourable treatment outlined by the global refugee regime on the implementation of provisions within the national refugee regime. The main argument of the article is that treating refugees the same as non-citizens, in accordance with these guiding standards, undermines the constitutional protection of refugees’ socio-economic rights. Refugees are not in the same circumstances as vulnerable non-citizens with permanent residence permits or special dispensation permits, nor are they in the same circumstances as historically disadvantaged citizens. The position of refugees in South African society is unique. Therefore, a special and differentiated approach to their treatment regarding access to socio-economic rights is recommended. It is argued that this approach should be considered and implemented in the spirit of substantive equality to achieve a key objective of the global refugee regime.